Analysis of Cohesive Devices in a Short Text: „Whiskey. No water. No Ice.“ by Tom Hart - Janković, Anita V. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The aim of this paper was two-fold. Primarily, based on literature review, it presented various takes on what makes a text and what makes it cohesive. Secondly, it reports the results of the cohesion analysis performed on a short drama by Tom Hart. This drama was written as a submission for the London Royal Court Theatre competition “100 Word Play”. The author used the model of analysis of a dramatic dialogue proposed by Halliday and Hassan. The dramatic dialogue here is characterized as a speaking text, for the stage; therefore, the stage directions were excluded from the analysis as para-linguistic phenomena. The results of the analysis revealed immediate ellipsis of anaphoric direction as the most common cohesive device in 47 percent of the text. Second in frequency are referencing mechanisms, and finally lexical devices and connectors. The analysis noted only one usage of verbal substitution. Furthermore, the analysis exposed the use of parallelisms, both lexical and structural, which are not predicted by the model. However, these instances were explained by Hoy’s model of complex lexical repetition. As text linguistics finds its use in writing in foreign language, it is recommended that the future research comparatively analyze cohesive devices in original and translated text for the purpose of raising awareness of different ways of building a text in different languages. In addition, the author suggests future analysis to include the coherence of a dramatic dialogue with stage directions as they contribute to the understanding of the text.